SOCIOECONOMIC OPTIMIZATION OF CREDIT SUBSIDIES FORAGRARIAN BUSINESS DEVELOPMENT PROJECTS - Tolmachev, Alexey; Valeryevich Smirnov, Vitaliy; Viktorovich Grishin, Evgeniy (Revista Inclusiones, 2020)
In modern agricultural business, an important role is assigned to social and economic criteria of effectiveness of decision-making aimed at regulating the development of agricultural business and the food market. Socio-economic assessment of projects for development of grain production entities with the participation of the state through subsidizing the lending process is necessary for improvement of functioning and growth dynamics of small, medium, and large-sized businesses. The social and economic criteria recommended by the authors are designed to encourage creating of new jobs, improve the standard of living of agribusiness participants and rural residents, and reduce social tension. It is noted that today there is a need in increase of investment activity, including improving quality of credit instruments that are being used. In this regard, the proposed method for determining the optimal level and limits of economic efficiency of credit subsidies for grain business development projects is important for the economy of the agro-industrial complex. All of the above indicates relevance of the research topic chosen by the author. The purpose of the author’s research was to develop a methodology for clarifying the quality indicators of credit security aimed at final performance. Scientific developments of domestic and foreign branch experts have been held for methodological basis of the research. For the information base, the author is using references and normative materials, periodical publications, data from Internet sources, logical techniques, and their own calculations. The research methods applied in the article are the following: abstract, monographic, comparative, computational, econometric, and economic. The results of using the method recommended by the author have showed the optimal level of compensation for the Bank credit rate under the current market conditions of 2.6% (with the current refinancing rate of 4.25%). This value will be the most profitable decision for the policy of state support, since it provides the most effective combination of factors of the tax burden (budget revenues), investment activity, the benefits of running a grain business, and achieving social and economic goals.